1994
DOI: 10.1021/bi00167a010
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-13 NMR analysis of intercompartmental flow of one-carbon units into choline and purines in Saccharomyces cerevisiae

Abstract: In Saccharomyces cerevisiae, the three-carbon of serine is normally the major one-carbon donor, although glycine and formate can substitute for serine. The second carbon of glycine enters via the glycine cleavage system in the mitochondria and can satisfy all cellular one-carbon requirements. It remains unresolved, however, as to the route by which these mitochondrial one-carbon units supply cytosolic anabolic processes. In the present work, we have used yeast mutants blocked at selected sites and 13C NMR to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 21 publications
3
58
0
Order By: Relevance
“…A second possibility is that formate production is defective in mitochondria from nonketotic hyperglycinemia patients. As we showed both in vitro with rat liver mitochondria (10,11), and in vivo with yeast (28,52), mitochondrial 5,10-methylene-THF is rapidly converted to formate and transported to the cytosol, where it is activated to 10-formyl-THF via cytoplasmic 10-formyl-THF synthetase (Fig. 1, mitochondrial reactions 3, 2, and 1 and cytoplasmic reaction 1).…”
Section: Discussionmentioning
confidence: 71%
“…A second possibility is that formate production is defective in mitochondria from nonketotic hyperglycinemia patients. As we showed both in vitro with rat liver mitochondria (10,11), and in vivo with yeast (28,52), mitochondrial 5,10-methylene-THF is rapidly converted to formate and transported to the cytosol, where it is activated to 10-formyl-THF via cytoplasmic 10-formyl-THF synthetase (Fig. 1, mitochondrial reactions 3, 2, and 1 and cytoplasmic reaction 1).…”
Section: Discussionmentioning
confidence: 71%
“…Evidence from both in vivo (9,10,45,54) and in vitro (6, 7) experiments supports a matrix localization for mitochondrial 1-carbon metabolism. Recently, we found that the MTHFD1L protein is tightly associated with the inner mitochondrial membrane, facing the matrix (37).…”
Section: Discussionmentioning
confidence: 84%
“…Coupling expression of purine pathway genes to those of one-carbon metabolism under these conditions may be required to maintain optimal functioning of the system as a whole. Additionally, induction of the one-carbon regulon would result in an increased contribution from mitochondrial one-carbon metabolism, which is metabolically closely linked with purine biosynthesis, because at least 25% of one-carbon units incorporated into purines are derived from mitochondrially derived formate, irrespective of the availability of cytoplasmic one-carbon units (44).…”
Section: Discussionmentioning
confidence: 99%